Length–Weight Relationship and Sexual Maturity Stages of Bluefish: Pomatomus saltatrix (L, 1766) in Tripoli Coast, Libya - Zahra Kashlut,; Sumaya Allamoushi, (AlQalam Journal of Medical and Applied Sciences, 2024)
Pomatomus saltatrix (L, 1766) is an important commercial fish in several countries, and that suffer from overfishing problems. In this study, 50 individuals of P. saltatrix were conducted during the fall, (October-November, 2022), on the Tripoli coast. Their total lengths and total weights were measured. The sex of the fish was determined, and the stages of sexual maturity were identified. The results showed that their lengths ranged 23.5-35cm, total weights 139-408g. The relationship between length and weight was negatively allometric, the number of males was higher than that of females, and all stages of sexual maturity were present. تعتبر سمكة المغرس من الأسماك التجارية الهامة في العديد من دول العالم، والتي تعاني من مشاكل الصيد الجائر. أجريت هذه الدراسة على 50 فرداً من سمكة المغرس خلال فصل الخريف (أكتوبر-نوفمبر 2022) بساحل طرابلس. وتم قياس أطوالها وأوزانها الكلية. وكذلك معرفة جنس السمكة وتحديد مراحل النضج الجنسي. أظهرت النتائج أن أطوالها تراوحت بين 23.5 – 35 سم، والأوزان الكلية 139 – 408 جرام. كانت العلاقة بين الطول والوزن الومترية سالبة، وعدد الذكور أعلى من عدد الإناث، وأن جميع مراحل النضج الجنسي موجودة